Positive politeness in Enola Holmes movie script - Mujahidah, Nisrina; Sumiati, Ati (Lililacs Journal, 2022)
The objectives of the study are to find the positive politeness strategies in a movie written by Jack Thorne. It is a descriptive qualitative study with data of the study were the dialogues in a movie script from Harry Bradbeer. The writer uses Brown and Levinson’s politeness strategy. This study focus on analyzing the types of positive politeness strategies used the most and what context behind the use of the strategies. The writer has found 107 data which mostly applied by Enola Holmes as the youngest character in the story. Meanwhile, the most widely used type of strategy is Strategy 12 because at that time, people in the Victorian era prioritized manners towards others, they tried to include the other person in the conversation so that no one felt left out. The study expected to use as part of learning positive politeness strategies and provide a reference for further research.